Empathy and Its Factors: Empirical Study - Dalia Antinienė; Rosita Lekavičienė (Lithuanian Sports University, 2018)
Background.  The  level  of  personality's  empathy  largely  determines  altruistic  behaviour  and  the  quality  of interpersonal relationships rendering the relevance of research indubitable. In psychology, empathy is classified into emotional/affective, cognitive and predictive. This study analyses affective empathy and aims to find out which personality traits related to self-perception, effectiveness in interpersonal relationships and sociodemographics are linked to empathy. Methods.  Research participants were schoolchildren, students, unemployed and employed individuals, inmates of  imprisonment  institutions  and  other  young  people. The  target  group  was  youth  from  17  to  27  years  of  age,   M =19.7, N =1400. An original measurement technique the psychometric quality indicators of which were sufficient (Cronbach's alpha reached .81) was used to research empathy. Results. The  means  of  Spearman's  correlation  coefficients  revealed  that  empathy  was  related  to  self-irony   (r = .19, p ≤ .001), externality (r = .14; p ≤ .05), positive self-evaluation (r = .47; p ≤ .001), leadership disposition   (r = .17; p ≤ .05), etc. Mann-Whitney and Kruskal-Wallis tests revealed that women (Mean Rank = 274.88) were more empathic than men (Mean rank = 139.78; p ≤ .001), young people with higher education (Mean Rank = 234.62) were more empathic than those with no or some education (Mean Rank = 161.06; p ≤ .001), etc. Conclusion. Research revealed that empathy was related to personal-psychological traits: self-irony, externality, positive self-evaluation, leadership disposition, general state of health, etc. The research highlighted the differences of empathy in different genders and revealed that women were more empathic than men. The research participants with high educational achievements exhibited the highest level of empathy. Keywords:  self-perception, interpersonal relationship effectiveness factors, sociodemographic factors